2019
DOI: 10.1186/s12902-019-0393-0
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the associations between gender and metabolic syndrome components in Korean adults: a national cross-sectional study

Abstract: Background This study aimed to examine the associations between gender and the prevalence of metabolic syndrome (MS) components among Korean adults by age and body mass index (BMI) subgroups. Methods This study obtained data from the sixth Korea National Health and Nutrition Examination Survey 2013–2015, a cross-sectional and nationally representative survey conducted by the Korean Centers for Diseases Control and Prevention. Results Of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
3
8
0
1
Order By: Relevance
“…Sex and age were other variables associated with metabolic syndrome. It was observed that males were 4.7 times more likely to have metabolic syndrome as compared to females, which is consistent with other reports (30). For one year increase in age, the likelihood of metabolic syndrome was higher by 6%, which is similar to a report from elsewhere (31).…”
Section: Resultssupporting
confidence: 91%
“…Sex and age were other variables associated with metabolic syndrome. It was observed that males were 4.7 times more likely to have metabolic syndrome as compared to females, which is consistent with other reports (30). For one year increase in age, the likelihood of metabolic syndrome was higher by 6%, which is similar to a report from elsewhere (31).…”
Section: Resultssupporting
confidence: 91%
“…Sex and age were other variables associated with metabolic syndrome. It was observed that males were 4.7 times more likely to have MetS as compared to females, which is consistent with other reports (30). For one year increase in age, the likelihood of MetS was higher by 6%, which is similar to a report from elsewhere (31).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, correlation of BMI with b-cell function and insulin and C-peptide responses were stronger in men, suggesting that there might be a need for different BMI cutoffs for risk evaluation based on sex. Epidemiologic studies have also reported a sex-related disparity in the prevalence of metabolic syndrome and type 2 diabetes (45). Women are diagnosed with type 2 diabetes at a higher BMI than men (46), suggesting that obesity could be defined differently according to sex, similar to the different cutoff values of waist circumference for men and women.…”
Section: Discussionmentioning
confidence: 99%